Multiple Roles of Lyn Kinase in Myeloid Cell Signaling and Function - Scapini, Patrizia (2009)
Lyn is a Src-family kinase (SFK) present in B-lymphocytes and myeloid cells. In these cell types Lyn establishes signaling thresholds by acting as both a positive and a negative modulator of a variety of signaling responses and effector functions. Lyn-deficiency in mice results in the development of myeloproliferation and autoimmunity. The latter has been attributed to the hyper-reactivity of Lyn-deficient B cells due to the unique role of Lyn in down-modulating B-cell receptor (BCR) activation, mainly through phosphorylation of inhibitory molecules and receptors. Myeloproliferation results, on the other hand, from the enhanced sensitivity of Lyn-deficient progenitors to a number Colony Stimulating Factors (CSFs). The hyper-sensitivity to myeloid growth factors may also be secondary to poor inhibitory receptor phosphorylation, leading to impaired recruitment/activation of tyrosine phosphatases and reduced down-modulation of CSF signaling responses. Despite these observations, the overall role of Lyn in the modulation of myeloid cell effector functions is much less well understood, as often both positive and negative roles of this kinase have been reported. In this review we discuss the current knowledge of the duplicitous nature of Lyn in the modulation of myeloid cell signaling and function.